Curb your enthusiasm. The complete first season [videorecording (DVD)] - Weide, Robert B.; David, Larry; Garlin, Jeff, 1962-; Hines, Cheryl; Danson, Ted, 1947-; Griffin, Kathy, 1960-; Lewis, Richard, 1947-; Louis-Dreyfus, Julia; Newman, Laraine, 1952-; Odenkirk, Bob, 1962-; Steenburgen, Mary; Vardalos, Nia, 1962- (HBO Video, 2004)
Larry's got it all: a loving wife, good friends, a successful career, and a great home. He is prone to speaking the unspeakable, honest to the point of insensitivity, Larry is a walking victim of misunderstandings and missed opportunities.